PENGUATAN NILAI -NILAI ISLAMI MELALUI KEGIATAN STUDI INTENSIF DI PONDOK PESANTREN AL MUHAMMAD CEPU - Rofiah Rofiah (Al Fattah Ejournal Sma Al Muhammad Cepu, 2023)
The development of modernization is accelerating and has a great impact on students. The negative effects of modernization must be prevented properly by strengthening Islamic values among students in a researcher discussing the strengthening of Islamic values in students through an intensive study program at the Al Muhammad Cepu Islamic Boarding School. The research method used is descriptive qualitative research using data collection procedures (observation, interviews, and documentation). The results of this study are the New Santri Ta'aruf Period (MASTASA) Memorization of The Basic Islamic Books, Intensive Islamic Studies at Pesantren Al Muhamamd Cepu. 2) Implementation of Strengthening Islamic Values through the Islamic Intensive Study Program at the Al Muhammad Cepu Islamic Boarding School including recitation of the Quran, and diniyah madrasah. 3) factors inhibiting the Strengthening of Islamic Values through the Islamic Intensive Study Program at the Al Muhammad Cepu Islamic Boarding School include lack of student discipline and lack of facilities and infrastructure.